1975
DOI: 10.1093/bja/47.5.575
|View full text |Cite
|
Sign up to set email alerts
|

ADVERSE REACTIONS TO INTRAVENOUS ANAESTHETICS: A Survey of 100 Reports

Abstract: One hundred consecutive reports of reactions to intravenous anaesthetics Althesin, thiopentone and Epontol are reviewed and analysed. Ten reactions are attributed to causes other than the anaesthetic drug, and four are believed to have been caused by the muscle relaxant employed. The remaining 86 reactions were grouped according to their clinical presentation: histaminoid reactions ( 19), histaminoid with bronchospasm (33), bronchospasm (12), cardiovascular collapse (uu), delayed histaminoid reactions (6), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1
1

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(21 citation statements)
references
References 25 publications
1
18
1
1
Order By: Relevance
“…These have been reviewed by Clarke et a1. 8 Dundee' found about thirty reported cases involving thiopentone, nineteen of which had been reported in the last 4 years. This may either represent an increasing incidence of the event or only an increase in the reporting of the events.…”
Section: Discussionmentioning
confidence: 99%
“…These have been reviewed by Clarke et a1. 8 Dundee' found about thirty reported cases involving thiopentone, nineteen of which had been reported in the last 4 years. This may either represent an increasing incidence of the event or only an increase in the reporting of the events.…”
Section: Discussionmentioning
confidence: 99%
“…In 1975 CLARKE et al [9] reported 100 adverse reactions to althesin in England, the incidence of these reactions to propanidid and althesin is claimed to be between 1 : 1000 and 1:7000 applications [5,10]. If on considers the great number of anaesthesia per year in every country of Europe the eminent clinical problem arising from such epidemiological studies is apparent.…”
mentioning
confidence: 99%
“…The second network of evidence that histamine was involved in adverse reactions to drugs used in anaesthesia and surgery was provided by British and Australian authors in the mid-1970s, who collected and clinically analysed hundreds of cases of more or less severe incidents to a variety of compounds (DUNDEE and WYANT 1974;SUTTON et al 1974;CLARKE et al 1975;FISHER 1975). These groups concentrated their interest on clinical features and predisposing factors for anaphylactoid reactions to drugs used in anaesthesia and surgery.…”
Section: Clinical Epidemiology Of Adverse Reactionsmentioning
confidence: 99%